Hypercoagulability biomarkers in Trypanosoma cruzi-infected patients - Pinazo, María-Jesús; Tassies, Dolors; Muñoz, Jose; Fisa, Roser; Posada, Elizabeth de Jesús; Monteagudo, Juan; Ayala, Edgar; Gállego, Montserrat; Reverter, Joan-Carles; Gascon, Joaquim (Thrombosis and Haemostasis, 2011)
There is a current controversy over the hypothesis that a number of thromboembolic events could be related to hypercoagulable state in patients with chronic Chagas disease. This study was designed to determine whether a prothrombotic state existed in chronic Trypanosoma cruzi-infected patients and, if so, to describe its evolution after treatment with Benznidazole. Twenty-five patients with chronic Chagas disease and 18 controls were evaluated. The markers used were prothrombin time, activated partial thromboplastin time, fibrinogen, antithrombin, plasminogen, protein C, total protein S, free protein S, factor VIII, D-dimer, activated factor VIIa, tissue-type plasminogen activator inhibitor-1, prothrombin fragment 1+2 (F1+2), plasmin-antiplasmin complexes, soluble P-selectin and endogenous thrombin potential (ETP). Despite statistically significant differences between cases and controls in several markers, only ETP (which quantifies the ability of plasma to generate thrombin when activated through tissue factor addition) (p<0.0001) and F1+2 (a marker of thrombin generation in vivo) (p<0.0001) showed values outside the normal levels in patients compared with controls. Similar results were obtained in these markers six months after treatment in the cohort of cases (p<0.0008 and p<0.004, respectively). These results may be relevant in clinical practice. Though current treatment for Chagas disease is still controversial, if it were considered as a thromboembolic risk factor the antiparasitic treatment strategy could be reinforced. The results also support further research on haemostasis parameters as candidates for early surrogate bio -markers of cure or progression of Chagas disease.
Keywords: Chagas Disease; hypercoagulability; biomarkers; prothrombin fragment 1+2; endogenous thrombin potential